PENGARUH FLUKTUASI KURS VALUTA ASING, INDEKS HARGA SAHAM INTERNASIONAL, DAN SUKU BUNGA BANK INDONESIA TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI BURSA EFEK INDONESIA (BEI) - B11111033, DANIEL LIMANTO (Jurnal Manajemen Update, 2015)
The purpose of this research is to how the fluctuation of foreign exchange rate,international composite stock index, and interest rate for composite stock index in Indonesiaif there have a positif effect or negatif effect. The sample that would be object of this reaserchis foreign exchange rate (US$/IDR), International Composite Stock Index (Dow Jones),Interest Rate of Indonesia Bank, and Jakarta Stock Exchange Composite Index. The methodof data collection is search in web-site in internet. The result of this research are there apositive effect because of change of foreign exchange rate and international composite stockindex for Jakarta Stock Exchange Composite Index and a negative effect because of changeof interest rate of Indonesia Bank. But there a unsignifikation of foreign exchange rate forJakarta Stock Exchange Composite Index and a signifikation of international composite stockindex and interest rate of Indonesia Bank for Jakarta Stock Exchange Composite Index.Keyword: Jakarta Stock Exchange Composite Index, Dow Jones, interest rate, IndonesiaBank, fluctuation.